PENGARUH AKUN INSTAGRAM @hijaberscommunityofficial TERHADAP PENGETAHUAN SYIAR ISLAM DAN FASHION HIJAB PADA FOLLOWERS MUSLIMAH - Lestari, Dea; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Instagram is one of the popular social media today, because Instagram provides many features to facilitate users in communication and Instagram is also a medium that can provide information that can be used by personal, organization, community and others. one of the communities using Instagram is an @hijaberscommunityofficial account. This account is the official Intagram account of the Indonesian hijabers community Hijabers Community, which contains Islamic syiar and fashion hijab. The theory used in this research is Stimulus - Response theory. The purpose of this research is to find out how big influence Instagram @hijaberscommunityofficial account of knowledge syiar Islam and fashion hijab on followers muslimah. This study uses quantitative research methods, with data collection techniques that is through the spread of questionnaires using google docs online to followers account Instagram @hijaberscommunityofficial with the number of samples of 384 determined by random sampling technique. Data analysis technique in this research using explanation statistic technique. The results of this study indicate that the level of Influence Account Instagram @hijaberscommunityofficial Against Knowledge Syiar Islam and Fashion Hijab On Muslimah followers have an enormous effect. It is seen from the simple regression in this research is equal to Y = 3,001 + 0,413X + e. Constant value equal to 3,001 and coefficient of variable of Instagram account value equal to 0,413. Meanwhile t count 24,579 bigger when compared with t table equal to 1,968, with significance level 0.000 smaller than α = 0,05. Based on the heel "Model Summary" shows that the value of R = 0.783, and the coefficient of determination (Rsquare) is equal to 0.613. This figure indicates that the influence of account instagram @hijaberscommunityofficial against the knowledge syiar islam and fashion hijab on Instagram @hijaberscommunityofficial followers of 61.3%. While the rest of 38.7% again influenced by other variables not included in this study.